Answer:
ngl, he does have a decent amount of subs for a beginner
Step-by-step explanation:
I would if I was allowed to
Answer:
h(x) = -16x² + 192x + 208
784ft
6 sec
13 sec
Step-by-step explanation:
a)
h(x) = -16x² +vx + h
here v represent velocity
represent initial height of launch
h(x) = -16x² + 192x + 208
b)
h(x) = -16x² + 192x + 208
here a = -16
b = 192
c = 208
x = -b/2a
= -192/2(-16)
= 6
plug this value in the equation
h(x) = -16(6)² + 192(6) + 208
= 784ft
e)
Plug h(x)=0 in the equation
0 = -16x² + 192x + 208
divide equation by -16
x² - 12x - 13 = 0
Factors
1x * -13x = -13
1x - 13x = -12
Factorised form
x² - 12x - 13 = 0
x² + x - 13x - 13 = 0
x(x+1) -13(x+1) = 0
(x+1)(x-13) = 0
x = -1
x = 13
Since time can not be negative so we will reject x = -1
Answer:
41
Step-by-step explanation:
an = a1 + (n-1)d
a_n = the nᵗʰ term in the sequence = 10
a_1 = the first term in the sequence = 5
d = the common difference between terms = 4
a10 = 5 + (10-1)4
a10 = 5 + (9)4
a10 = 5 + 36
a10 = 41
Answer:
A = (5s^2t - 9st) (3t + 1)
Step-by-step explanation:
(5s^2 - 9s) (3t^2 + t)
= 15s2t^2 + 5s^2t - 27st^2 - 9st
= 5s2t (3t + 1) - 9st (3t + 1)
= ( 5s^2t - 9st) (3t+1)
Answer:
y=0
Step-by-step explanation:
6y+2=-2(2y-1)
Distribute
6y+2 = -4y +2
Add 4y to each side
6y+2 = -4y +2+4y
6y +2 =2
Subtract 2 from each side
6y +2-2 = 2-2
6y = 0
y=0